Robot-mediated impairment-oriented and task-specific training on upper limb post stroke: feasibility and preliminary effects on physical function and quality of life - Tay, San San; Zhang, Fuquan; Visperas, Christine Alejandro; Koh, Xuan Han; Lau, Borisut; Neo, Jin Rui Edmund (Frontiers in Neurology, 2024)
Objective To assess the feasibility and safety of conducting robot-mediated impairment training (RMIT) and robot-mediated task-specific training (RMTT). The device deployed is the Optimo Regen (OR®), capable of delivering both impairment-oriented training and task-specific training. Methods This was a single-centre, randomized, single-blinded, two-arm, parallel group, controlled trial. Patients fulfilling criteria were randomized into either the RMIT or RMIT + RMTT group and provided with 20 h of robotic therapy on top of standard care. Results A total of 4 patients were recruited, with 2 patients receiving treatment in each arm. The study was feasible, with a 66.7% enrolment rate, 75% completion rate, and 100% attendance for each intervention session. We achieved a 90% satisfaction rate with no serious adverse effects. All patients had improvement of motor power, Fugl-Meyer Assessment-Upper Extremity (FMA-UE), Functional Independence Measure (FIM), Hospital Anxiety and Depression Scale (HADS), and quality of life scores at 1 month. FIM continued to improve at 3 months post-commencement of intervention. There was relative ease of use of the device. Conclusion This trial is feasible. A full-scale study is warranted, to compare RMIT against RMTT, which is a novel application.